Homogeneous transformation matrix for force-torque sensor orientation compensation in rotatable control handle - Shivam Suresh Zagade; Rajiv Basavarajappa H.; Sudhir Madhav Patil; Abhishek Pradeep Buzruk; Kshitij Ghanshyam Jiwane; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
The high inertia ceiling suspended systems with multiple degrees of freedom uses power assist technologies to reduce operator’s burden to operate the machine. Such systems are popularly used in medical diagnostic systems, construction machines, material handling, automotive, and aerospace assembly lines. These systems commonly use multi-axis force-torque (FT) sensor to sense the forces applied by user on rotatable control handle. These sensed forces are utilized by power assist algorithm to drive system in required direction with the help of electrical motor drives. The rotatable control handle used to control the machine poses a significant obstacle for maintaining alignment between FT sensor co-ordinate frame and the system’s base frame. This research paper focuses on the development of homogeneous transformation matrix to compensate for any change in FT sensor orientation caused by rotation of control handle. The homogeneous transformation matrix developed in this research paper, transforms the force and torque values measured by FT sensor with respect to system base frame. This adaptive technique provided seamless control of the power assist ceiling suspended system from different directions during handling and movement. This helped to enhance control and flexibility of power assist ceiling suspended system.